POLICY NETWORK ANALYSIS ON FOREST AND LAND FIRE AT PELALAWAN REGENCY - Adiwijoyo Adiwijoyo; Heri Purnomo; Suria Darma Tarigan (Jurnal Kebijakan Publik, 2026)
Forest and land fires in Pelalawan Regency, Riau Province, represent a persistent and multidimensional environmental governance challenge shaped not only by ecological factors, but also by land-use change dynamics, plantation expansion, and the complexity of cross-sectoral and multi-level policy networks. This study aims to examine the interrelationships among land cover change, hotspot dynamics, and the structural configuration of the forest and land fire control policy network in Pelalawan Regency. The research adopts an integrated approach combining spatial analysis and policy network analysis. Spatial analysis assesses land cover change and the distribution of fire hotspots for the 2000–2022 period using Terra and Aqua satellite data from the Moderate Resolution Imaging Spectroradiometer (MODIS) with a confidence level of ≥50%, overlaid with land cover data from the Ministry of Environment and Forestry. Subsequently, policy network analysis is conducted using a Social Network Analysis (SNA) approach applied to 53 regulatory instruments at the national, provincial, and regency levels, measuring degree centrality, betweenness centrality, closeness centrality, and eigenvector centrality. The findings indicate that hotspot surges prior to 2016 are strongly correlated with plantation expansion and weak policy implementation effectiveness, despite the presence of an extensive normative regulatory framework. Law No. 32/2009 is identified as the most central normative node within the policy network, while the strengthening of operational policies after 2016 has contributed significantly to the reduction of forest and land fire incidents. This study underscores that the effectiveness of forest and land fire control is determined not by regulatory proliferation, but by the integration of policy networks and cross-sectoral implementation capacity.